Evaluasi Tingkat Pembelajaran PJOK di SMA Negeri 1 Bangsri pada Masa Pandemi Covid-19 Tahun Ajaran 2021/2022 - Alfian Wira Setiaji; Cahyo Yuwono (Indonesian Journal for Physical Education and Sport, 2022)
At the end of 2019 the world was shocked by the presence of the corona virus disease that circulated in Indonesia and spread very quickly to all corners of the world. The emergence of the Covid-19 pandemic caused changes in the education sector. The way the Indonesian government stops the spread is to make activities different from previous years, which used to be face-to-face, replaced by the application of distance learning technology from home. Therefore, the problem of this research is how to evaluate the level of PJOK learning at SMA Negeri 1 Bangsri during the Covid-19 pandemic for the 2021-2022 academic year. The purpose of this study was to describe the implementation of PJOK learning at SMA Negeri 1 Bangsri during the Covid-19 pandemic. This study uses a qualitative method with a descriptive approach. The results of the study were seen from the learning implementation process starting from planning to make syllabus, lesson plans, learning media, teaching materials that were adjusted during the Covid-19 pandemic. The implementation of learning from home is prioritized to provide valuable experiences during the Covid-19 pandemic through online. The assessment system uses 3 aspects, namely affective, cognitive and psychomotor which have been adapted to during the Covid-19 pandemic.